Contactless temperature determination using dual-channel lock-in phosphor thermometry - Hashemi, Amir; Jovicic, Gordana; Batentschuk, Miroslaw; Brabec, Christoph; Vetter, Andreas (Measurement Science and Technology, 2017)
In this paper, we present dual-channel lock-in phosphor thermometry, which offers an option of accurate and contactless temperature determination under high environmental noise. We studied YAG:Dy as thermographic phosphor at an excitation wavelength of 405 nm. We tested our approach under different experimental conditions with noise levels of about 550, 1060 and 2190 times larger than the excitation signal. With the dual-channel lock-in setup, we were able to suppress the strong noise in all cases and to reliably determine surface temperature using our optical measurements (error < 10 K). Additionally, the effect of signal to noise ratio, lock-in frequency and lock-in bandwidth on temperature determination accuracy was studied in this work.
Keywords: dual-channel; lock-in; luminescence; phosphor thermometry; temperature

Gas Phase Phosphorescence Thermometry Applied in Free Air Jet and Pressurized Test Cell - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (European Combustion Meeting 2013, 2013)

Influence of electric fields on premixed laminar flames: visualization of perturbations and potential for suppression of thermoacoustic oscillations - Kuhl, Johannes; Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (35th International Symposium on Combustion, 2014)

Influence of electric fields on premixed laminar flames: Visualization of perturbations and potential for suppression of thermoacoustic oscillations - Kuhl, Johannes; Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (Proceedings of the Combustion Institute, 2015)
In the second part the potential of electric fields to suppress acoustic flame instabilities was studied on a flat flame using the high-speed detection of the flame chemiluminescence. Acoustic oscillations were generated by an injector with defined injection frequencies resulting in a periodically lifted flame. Depending on the electric field strength the duration of flame oscillation could be reduced by up to 54%, so the flame returns quicker to its initial condition. (C) 2014 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Laminar flame; Flame control; Electric field; PLIF; PIV

Infrared Absorption Imaging of Water Ingress Into the Encapsulation of (Opto-)Electronic Devices - Hepp, Johannes; Vetter, Andreas; Langner, Stefan; Woiton, Michael; Jovicic, Gordana; Burlafinger, Klaus; Hauch, Jens; Camus, Christian; Egelhaaf, Hans-Joachim; Brabec, Christoph (IEEE Journal of Photovoltaics, 2019)
Water ingress into the encapsulation of electronic devices is a serious issue, especially for organic and perovskite-based electronics. In order to guide the development of suitable barrier materials and design, a reliable, fast, and non-destructive analysis tool is required. In this work, an imaging setup is presented, which is based on selective infrared (IR) radiation sources and a mid-IR sensitive camera that uses the absorption hand of water around 1920 nm and a reference band. This system enables us to monitor the distribution of water concentration inside the packaging of devices and its change over time. Our measurement is capable of detecting the local presence of water down to the mg/m(2) concentration range in a wide variety of encapsulation materials. The new tool allows identifying the pathways of moisture ingress into the encapsulation along with the corresponding diffusion coefficient. Thus, it provides fast and reliable analysis of humidity related failure mechanisms, and consequently helps to improve the design of encapsulation materials and processes.
Keywords: Degradation; diffusion processes; optical signal detection; organic photovoltaics (PVs); packaging

Luminescence properties of the thermographic phosphors Dy3+:YAG and Tm3+:YAG for the application in high temperature systems - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2015)
Keywords: Laser-Induced Phosphorescence; Thermographic Phosphors; Phosphor Thermometry

Luminescence Properties of the Thermographic Phosphors Dy3+:YAG and Tm3+:YAG for the Application in High Temperature Systems - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2015)
The high temperature sensitivity of the luminescence emission of thermographic phosphor (TP) particles favours its utilization for the measurement of wall or gas temperatures in combustion devices. The present work focuses on the luminescence behavior and suitability of two lanthanide ion types (Tm and Dy) doped in a YAG host crystal for high temperature applications. The Dy: YAG is awell-known thermographic phosphor and is used here as a reference for the comparison with Tm: YAG TP. Additionally its dopant concentration is varied to improve its signal intensity for high temperature applications. For the studied thermographic phosphors phosphorescence spectra, intensity ratios and luminescence decay time are characterized for awide temperature range up to 1573 K.
Keywords: Laser-Induced Phosphorescence; Phosphor Thermometry; Thermographic Phosphors

Phosphor thermometry in turbulent hot gas flows applying Dy:YAG and Dy:Er:YAG particles - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (Measurement Science & Technology, 2015)
In order to improve the phosphorescence emission behavior of phosphor powders for temperature measurements in a gas flow, the activator concentration in Dy:YAG was varied and the phosphor was co-doped with the sensitizer erbium (Er). Phosphorescence spectra, overall phosphorescence signal intensities and the phosphorescence lifetime were characterized in a furnace up to 1400 K. Planar thermometry was conducted in hot gas flows, whereby an improved average temperature uncertainty of about 3% was obtained using Dy:YAG and of 1.8% for Dy:Er:YAG for temperatures of 450 K.
Keywords: thermographic phosphors; laser-induced phosphorescence; gas phase thermometry

Simultaneous thermometry and velocimetry in hot gas flows using laser-induced phosphorescence - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (Kick-off Symposium Optical Imaging Center Erlangen, 2013)

Temperature measurements using YAG : Dy and YAG : Sm under diode laser excitation (405 nm) - Hashemi, Amir; Vetter, Andreas; Jovicic, Gordana; Batentschuk, Miroslaw; Brabec, Christoph (Measurement Science & Technology, 2015)
Temperature-sensitive phosphors offer an option of accurate contactless temperature measurement. The method can be applied to a wide temperature range and up to more than 1500 K. In the current paper, phosphor thermometry based on four rare earths doped in YAG was studied. The standard excitation of thermographic phosphors is carried out with a Nd : YAG laser often at 355 or 266 nm. We examined the temperature dependent luminescence at an excitation wavelength of 405 nm. The excitation with visible blue light offers two main advantages: the excitation sources are rather cheap and they involve less safety issues. Accordingly, a variety of new application of such remote-thermometry would be possible. The results show that YAG : Dy and YAG : Sm may be well utilized for phosphor thermometry excited by a 405 nm diode laser.
Keywords: phosphor thermometry; temperature; luminescence; phosphorescence; diode laser

Temperatur- und Geschwindigkeitsbestimmung in Gasströmen mittels laserinduzierter Phosphoreszenz - Jovicic, Gordana; Zigan, Lars; Will, Stefan; Leipertz, Alfred (26. Deutscher Flammentag, 2013)